Sacubitril/valsartan versus valsartan in regressing myocardial fibrosis in hypertension: a prospective, randomized, open-label, blinded endpoint clinical trial protocol - Lee, Vivian; Zheng, Qishi; Toh, Desiree-Faye; Pua, Chee Jian; Bryant, Jennifer A.; Lee, Chi-Hang; Cook, Stuart A.; Butler, Javed; Díez, Javier; Richards, A. Mark; Le, Thu-Thao; Chin, Calvin W. L. (Frontiers in Cardiovascular Medicine, 2023)
Background: Diffuse interstitial myocardial fibrosis is a key common pathological manifestation in hypertensive heart disease (HHD) progressing to heart failure (HF). Angiotensin receptor-neprilysin inhibitors (ARNi), now a front-line treatment for HF, confer benefits independent of blood pressure, signifying a multifactorial mode of action beyond hemodynamic regulation. We aim to test the hypothesis that compared to angiotensin II receptor blockade (ARB) alone, ARNi is more effective in regressing diffuse interstitial myocardial fibrosis in HHD. Methods: REVERSE-LVH (Role of ARNi in Ventricular Remodeling in Hypertensive LVH) is a prospective, randomized, open-label, blinded endpoint (PROBE) clinical trial. Adults with hypertension and left ventricular hypertrophy (LVH) according to Asian sex-and age-specific thresholds on cardiovascular magnetic resonance (CMR) imaging are randomized to treatment with either sacubitril/valsartan (an ARNi) or valsartan (an ARB) in 1:1 ratio for a duration of 52 weeks, at the end of which a repeat CMR is performed to assess differential changes from baseline between the two groups. The primary endpoint is the change in CMR-derived diffuse interstitial fibrosis volume. Secondary endpoints include changes in CMR-derived left ventricular mass, volumes and functional parameters. Serum samples are collected and stored to assess the effects of ARNi, compared with ARB, on circulating biomarkers of cardiac remodeling. The endpoints will be analyzed with reference to the corresponding baseline parameters to evaluate the therapeutic effect of sacubitril/valsartan versus valsartan. Discussion: REVERSE-LVH will examine the anti-fibrotic potential of sacubitril/valsartan and will offer mechanistic insights into the clinical benefits of sacubitril/valsartan in hypertension in relation to cardiac remodeling. Advancing the knowledge of the pathophysiology of HHD will consolidate effective risk stratification and personalized treatment through a multimodal manner integrating complementary CMR and biomarkers into the conventional care approach. Clinical trial registration and ethics: The study is registered at ClinicalTrials.gov (Identifier: NCT03553810). Ethical approval was granted and is reviewed annually by the SingHealth Centralised Institutional Review Board (CIRB ref: 2018(CIRB ref: 2018/2182).